2008
DOI: 10.1007/s00586-008-0731-9
|View full text |Cite
|
Sign up to set email alerts
|

Posterior fusion only for thoracic adolescent idiopathic scoliosis of more than 80°: pedicle screws versus hybrid instrumentation

Abstract: The treatment of thoracic adolescent idiopathic scoliosis (AIS) of more than 80°traditionally consisted of a combined procedure, an anterior release performed through an open thoracotomy followed by a posterior fusion. Recently, some studies have reassessed the role of posterior fusion only as treatment for severe thoracic AIS; the correction rate of the thoracic curves was comparable to most series of combined anterior and posterior surgery, with shorter surgery time and without the negative effect on pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
2
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 51 publications
2
93
2
11
Order By: Relevance
“…Hwang et al [30] assessed skipped pedicle screw fixation in 57 patients with 5-year follow-up and noted minimal loss of correction from the immediate post-op (2 %), but did not remark on any changes at the 2-year interval. Di Silvestre et al [11] compared hybrid and pedicle screw constructs with a mean follow-up of 6.7 years and found better maintenance of correction with screws. They noted a mean loss of 11.3°with hybrid constructs as compared to 1.9°using screws (p = 0.0005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hwang et al [30] assessed skipped pedicle screw fixation in 57 patients with 5-year follow-up and noted minimal loss of correction from the immediate post-op (2 %), but did not remark on any changes at the 2-year interval. Di Silvestre et al [11] compared hybrid and pedicle screw constructs with a mean follow-up of 6.7 years and found better maintenance of correction with screws. They noted a mean loss of 11.3°with hybrid constructs as compared to 1.9°using screws (p = 0.0005).…”
Section: Discussionmentioning
confidence: 99%
“…In 1995, Suk et al [5] reported outcomes in 78 patients and noted improved coronal correction and less loss of correction at 2 years using screws when compared to hybrid constructs. Subsequently, other studies have shown pedicle screw constructs to provide greater immediate postoperative correction of coronal curvature, axial translation, and axial rotation [11][12][13]. Better maintenance of correction at 2 years has been reported in both fused and compensatory curves, as well as a reduction in the number of segments fused and a lower revision rate associated with pedicle screw constructs [12,15,16].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies [18] have shown a correction rate in severe scoliosis treated by all-screw posterior instrumentation to be around 50 %, which is similar to the correction rate obtained by combined approach surgery. Di Silvestre et al [19] compared two similar series of patients with severe thoracic idiopathic scoliosis (main curve over 80°Cobb), the first treated by posterior hybrid instrumentation fusion and the second by posterior all-screw instrumentation fusion, with a mean follow-up of 6.7 years. They reported a thoracic curve correction rate of 44.52 % in patients treated by hybrid instrumentation versus 52.4 % in patients treated by all-screw instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…Authors stated that all-screw constructs result in a negligible loss of correction at follow-up compared with that observed with hybrid constructs and especially with hook constructs [6,7,32,33]. It is speculated that this loss of reduction is due, in great part, to the instability of the anchorages.…”
Section: Discussionmentioning
confidence: 99%